Effect of Blue Pea Flower (Clitoria ternatea) Infusion on Blood Pressure and Sleep Quality in Individuals with Prehypertension - Ardha, Nabilah Shofiyyah; Savira, Maya; Fitri, Aida; Lintang, Letta Sari (Universitas Muhammadiyah Purwokerto, 2026)
Prehypertension is a condition in which blood pressure is above the normal range but has not yet reached the threshold for hypertension. This condition increases the risk of developing hypertension and cardiovascular diseases and is also associated with decreased sleep quality. One nonpharmacological approach that may help reduce blood pressure while improving sleep quality is the regular consumption of butterfly pea flower (Clitoria ternatea) infusion. Objective: This study aimed to analyze the effect of Clitoria ternatea infusion on blood pressure and sleep quality in individuals with prehypertension. This study employed a one-group pretest–posttest experimental design. A total of 34 participants with prehypertension were recruited using purposive sampling. Data were analyzed using the Wilcoxon Signed Rank Test. After the intervention, the mean systolic blood pressure decreased to 113.71 ± 8.09 mmHg and diastolic blood pressure to 73.00 ± 4.52 mmHg. The mean heart rate decreased to 73.97 ± 7.14 beats per minute, and the mean Pittsburgh Sleep Quality Index (PSQI) score improved to 4.41 ± 0.96. Statistical analysis showed significant reductions in systolic and diastolic blood pressure, heart rate, and a significant improvement in sleep quality, as indicated by a decrease in PSQI scores (p < 0.001). This study concludes that the administration of Clitoria ternatea infusion is associated with a reduction in blood pressure and an improvement in sleep quality among individuals with prehypertension.